The average rate of change in a function is determined by :
![=(f(b)-f(a))/(b-a)](https://img.qammunity.org/2023/formulas/mathematics/high-school/is9oz8o31xmu8i20idkaxcrabm7dty5fgp.png)
Where :
a = lower limit
b = upper limit
f(a) = value of the function at the lower limit
f(b) = value of the function at the upper limit
From the given problem :
![-7\leqslant x\leqslant6](https://img.qammunity.org/2023/formulas/mathematics/college/rdfde3w7amkdrx3sw9nv0068fm1ljm02rr.png)
The lower limit is -7 and the upper limit is 6.
So we can say that a = -7 and b = 6
Looking at the figure when x = -7, f(x) = -10
when x = 6, f(x) = -5
Then we can also say that f(a) = -10
and f(b) = -5
Substitute the given values to the formula :
![=(-5-(-10))/(6-(-7))](https://img.qammunity.org/2023/formulas/mathematics/college/zlz8x7aenou5syn1sq504bw20farw8q5rm.png)
![=(5)/(13)](https://img.qammunity.org/2023/formulas/mathematics/college/z27ufdmx9bl4nqanmwezxhr0dmq99hld6f.png)
Therefore, the average rate of change is :
![(5)/(13)](https://img.qammunity.org/2023/formulas/mathematics/college/xchqx081k5zcjcie573u8fvvpy1ec5gb9a.png)